Pola Asuh Gizi, Tingkat Konsumsi dan Kejadian Stunting Pada Anak Balita Usia 6-24 Bulan di Wilayah Kerja Puskesmas Woha Kabupaten Bima - Diansa Fitri; Sulistiyani Sulistiyani; Ruli Bahyu Antika (Jurnal Kesehatan, 2022)
Growth retardation is a chronic nutritional condition caused by long-term lack of nutrients due to inadequate nutritional needs in the diet, causing adults to have an inappropriate posture for their age. Stunting malnutrition is a form of malnutrition resulting from the calculation of height for age (height/age) below standard deviation (< -2 SD). Woha sub-district is the district with highest rate of stunting children in Bima province based on the results of nutrition status moniitoring in 2018 up to 39.65%, but decreased in 2019, specifically 33.1%. This study aimed to find out the relationship between nutritional care, consumption, stunting rates among children aged 6-2 months in the work area of ​​Puskesmas Woha, Bima Regency. This study used a cross-sectional study design. The sampling method used a simple random sampling technique, probability sampling. Data analysis using chi-squared statisticcal test. The bivariate test showed a limited relationship between energy consumption (p = 0.00 ), protein (p = 0.020), iron (p = 0.038) and zinc (p = 0.009). However, there was no relationship between the degree of calcium absorption (p = 0.38 ) and the prevalence of stunting. There was a relationship between parental nutritional levels and energy consumption (p = 0.026). However, there was no relationship between parental nutritional levels and the consumption of protein (p = 0. 32), calcium (p = 0.130), iron (p = 0.078) and zinc (p = 0.281) in children from 6 to 2 months old in this Region. Woha Community Health Center, Bima Regency. There was no relationship between maternal nutritional knowledge and stunting rate (p = 0.21 ). There is a relationship between parental nutrition and the prevalence of stunting (p = 0.007) in children 6–2 months of age at Woha Community Health Center, Bima Regency